2020
DOI: 10.1371/journal.pone.0240542
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and survival in hepatocellular carcinoma in the United States and Taiwan

Abstract: Background Survival in hepatocellular carcinoma (HCC) is lower in the USA than in Taiwan. Little is known about the extent to which differences in stage at diagnosis and treatment contribute to this difference. We examined treatment patterns and survival in HCC and analyzed factors driving the difference. Methods Using a uniform methodology, we identified patients aged 66 years and older with newly diagnosed HCC between 2004 and 2011 in the USA and Taiwan. We compared treatment within 6 months after HCC diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…that are not available from cancer registries. Our study also has several limitations, including treatment data obtained from registry linkage that is not as detailed as those from clinical studies, and given the unique treatment paradigms of HCC, inaccuracy reporting of treatment in registry is possibile [ 35 ]. Information on liver function, an important determinant of HCC outcome, was not available in this study.…”
Section: Discussionmentioning
confidence: 99%
“…that are not available from cancer registries. Our study also has several limitations, including treatment data obtained from registry linkage that is not as detailed as those from clinical studies, and given the unique treatment paradigms of HCC, inaccuracy reporting of treatment in registry is possibile [ 35 ]. Information on liver function, an important determinant of HCC outcome, was not available in this study.…”
Section: Discussionmentioning
confidence: 99%
“…in Italy. [113][114][115][116] However, Asian cases also show earlier cancer stages despite younger ages, 107 which indicates that Asian patients tend to receive more HCC surveillance and be diagnosed in earlier stages.…”
Section: Differences Were Found In Demographic Characteristics Betweenmentioning
confidence: 99%
“…Most of the clinical cases found in outpatient may belong to the middle and advanced stages, and there were very few cases that can get the best surgical treatment. In a clinical study, it showed that the differential stage at diagnosis and treatment were substantially associated 29 Obviously, if the proportion of early cases is high, the overall survival rate will be high. 30 Liver cancer screening may be able to detect more early cases, lead to effective early treatment which will benefit the therapeutic effect of liver cancer and improve its survival rate.…”
Section: Discussionmentioning
confidence: 99%